The Effect of Fennel on Pain Relief in Primary Dysmenorrhea: A Systematic Review of Clinical Trials - Mojgan Nazari; Masoumeh Rostami-Moez; Fatemeh Ebrahimi (Shahrekord University of Medical Sciences, 2020)
Background and aims: Fennel is often advocated for primary dysmenorrhea. Whether this herb has a real effect on pain relief is still a matter of debate in medicine. Therefore, this study was conducted to evaluate the effect of fennel on primary dysmenorrhea. Methods: This systematic review was conducted on clinical trials (non-randomized, randomized, historical study with concurrent control) published in PubMed (MEDLINE), Web of Science, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), ProQuest, and Persian databases (Magiran, IranMedex, SID, Irandoc) regarding the effect of fennel on pain intensity in primary dysmenorrhea from 1990 to 2019. Nine studies met all inclusion criteria. Any clinical trials on young women with primary dysmenorrhea were included in the study. Studies that used fennel plus other products investigated fennel effect on premenstrual syndrome (PMS) and bleeding; studies without a control group and nonclinical trials were excluded. In all studies, participants were young female university or high school students. All of them had moderate to severe primary dysmenorrhea. Results: In all of the studies except for one, fennel had been more effective than placebo in pain relief (P<0.01). Non-steroidal drugs had the same result as fennel for pain relief. However, in one study, the difference between non-steroidal anti-inflammatory drugs (NSAIDs) and fennel in pain relief was observed. Only one study reported increasing vaginal bleeding after fennel consumption in some cases. Conclusion: Collectively, these studies favored fennel over NSAID, other herbal drugs, and placebo. But more investigation is needed to draw a firm conclusion.